Enhancing Continuous Assessment in Jigawa State Senior Secondary Schools: The Impact of Electronically Processed Data (British Journal of Multidisciplinary and Advanced Studies, 2024)
This journal article explores the relationship between electronically processed data and continuous assessment in senior secondary schools in Jigawa State. The study investigates the potential benefits of using electronic data processing methods in continuous assessment and evaluates their impact on student performance and educational outcomes. Through a mixed-methods approach involving qualitative interviews with teachers and quantitative analysis of student data, the research provides valuable insights into the advantages of electronic data processing in improving the efficiency, accuracy, and effectiveness of continuous assessment practices. The findings demonstrate the transformative potential of electronic data processing in enhancing educational outcomes and informing instructional decisions. Based on the results, the article provides recommendations for successful implementation and future research directions.